The Effect of Law on Hate Crime Reporting: The Case of Racial and Ethnic Violence - Stacey, Michele (American journal of criminal justice, 2015)
Drawing on Jenness and Grattet’s ( 2001 ) typology of hate crime law as well as theories about the relationship between minority group status and victimization, this analysis examines how different definitions of hate crime produce variation in the reported prevalence of anti-racial and anti-ethnic hate crime. This study uses data from the Uniform Crime Reports and a panel modeling structure to examine the factors that contribute to reported anti-Black and anti-Hispanic hate crime levels. It was hypothesized that broader hate crime definitions would result in greater levels of reported hate crime; however, the results suggest that the definition of hate crime influences the reported prevalence of anti-Hispanic hate crime, but that variation in law does not affect anti-Black hate crime once demographic and other structural characteristics are taken into account. Future research and policy should consider how these differences in definition could influence the handling of hate crime cases at all levels.